The Influence of Concentration on the Formation of Chemical Bath Deposited Copper Tin Sulphide Thin Films: SEM and EDX Studies (Journal of Chemical Engineering Research Updates, 2022)
Nanostructured copper tin sulphide films have been deposited on the substrate (soda lime glass) via an economical chemical bath deposition method. The scanning electron microscopy (SEM) technique and energy dispersive X-ray analyzer (EDX) method were employed in this work to study the films’ morphology and composition. The EDX data and SEM images confirmed that the content of elements (sulfur, tin, and copper), the shape, and the grain size strongly depended on the concentration of the precursors during the formation of films. Experimental results revealed that a higher atomic percentage of the element could be observed for the films prepared using a higher concentration of solution during the experiment.
Keywords: Thin films; Semiconductor; Ternary compound; Metal chalcogenide; Chemical bath deposition